Implant Site Nexplanon Reaction? - Pedroso, C (2015)
Nexplanon (Schering-Plough Limited/Merck Sharp & Dohme Limited (MSD)) is a long active reversible contraceptive method that provides effective contraception for 3 years. It consists of a single, flexible, rod-shaped implant, containing 68 mg etonogestrel. It is 4 cm long, consists of an ethylene vinyl acetate copolymer, a non-absorbable material, and also contains 15 mg of barium sulfate, which makes it visible by X-ray. We describe a case of a 39-year-old woman who experienced a local reaction to the barium sulfate in Nexplanon. She was given medical treatment, but only the removal of the implant resolved the symptoms. After removal there was gradual improvement and 72 h later the patient was asymptomatic. Allergic reaction to barium sulfate is extremely rare: until now, there have only been two cases associated with Nexplanon described in the literature.